2021
DOI: 10.1002/jum.15633
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Ultrasound Education in United States Medical Schools

Abstract: Objectives Ultrasound is used by nearly every medical specialty. Medical schools are integrating ultrasound education into their curriculum but studies show this to be inconsistent. The purpose of this study was to provide an updated description of ultrasound in the curricula of United States Accredited Medical Schools (USAMS). Methods In 2019, USAMS curricular offices were contacted. Institutions were asked about the presence of ultrasound curriculum and for contact information for faculty involved with educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Our experience has demonstrated that some of these limitations can be overcome by incorporating students as instructors of their classmates and students' self-learning by web-based POCUS modules (15,16). There are unresolved issues of ultrasound education in medical schools, such as duration of the instruction and knowledge retention at the final year of the medical school (17,18). The introduction of ultrasound in the preclinical years, it's teaching in clinical courses and clinical rotations, and tested in practical exams could reinforce further this knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience has demonstrated that some of these limitations can be overcome by incorporating students as instructors of their classmates and students' self-learning by web-based POCUS modules (15,16). There are unresolved issues of ultrasound education in medical schools, such as duration of the instruction and knowledge retention at the final year of the medical school (17,18). The introduction of ultrasound in the preclinical years, it's teaching in clinical courses and clinical rotations, and tested in practical exams could reinforce further this knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the advantage of motivated student leadership, as it is often cited that faculty resources are a rate-limiting step in ultrasound education. 1 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…Point of care ultrasound (POCUS) training in undergraduate medical education (UME) is becoming increasingly more prevalent and standardized, yet the most recent analysis found that greater than 25% of US medical schools lack an ultrasound curriculum. 1 The need for ultrasound education in UME is increasingly recognized by published consensus statements, 2 , 3 and recently the Canadian Ultrasound Consensus for Undergraduate Medical Education outlined 85 ultrasound curricular elements recommended for inclusion in UME. 4 Despite need, integrating longitudinal ultrasound curriculum as accomplished at institutions like the University of South Carolina 5–7 is costly and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The power of POCUS to augment patient care decisions and the increasing availability of portable ultrasound technology have led to a rapid expansion of POCUS training in medical education. National surveys of educational leaders indicate that 73% of medical schools 6 and 40% of internal medicine (IM) residency programs 7 have POCUS training programs. Professional organizations within IM, including the American College of Physicians 8 and the Society of Hospital Medicine, 9 are increasingly advocating for POCUS education.…”
Section: Introductionmentioning
confidence: 99%